Altitudinal dependence of evening equatorial F region vertical plasma drifts. Issue 7 (22nd July 2014) - Fejer, B. G.; Hui, D.; Chau, J. L.; Kudeki, E.
Abstract We use Jicamarca incoherent scatter radar measurements to study for the first time the altitudinal variations of late afternoon and early night equatorial F region vertical plasma drifts. We also present the initial vertical drift measurements over the altitudinal range from about 200 to 2000 km. These data show that the afternoon drifts decrease weakly with altitude. Near their evening prereversal enhancements, the vertical drifts generally increase with altitude below about the F layer peak, decrease with height near the F layer peak and above, and are nearly height independent in the (solar flux dependent) topside ionosphere. The transition altitudes from height‐decreasing to height‐independent evening upward drifts decrease with altitude from solar maximum to solar minimum. After their reversal to downward, the vertical drifts do not change much with height. The altitudinal dependence of the evening vertical drifts has large day‐to‐day variability and is closely related to the time dependence of the zonal drifts, as expected from the curl‐free electric field condition.